Proteome analysis for downstream targets of oncogenic KRAS--the potential participation of CLIC4 in carcinogenesis in the lung. - Koji Okudela; Akira Katayama; Tetsukan Woo; Hideaki Mitsui; Takehisa Suzuki; Yoko Tateishi; Shigeaki Umeda; Michihiko Tajiri; Munetaka Masuda; Noriyuki Nagahara; Hitoshi Kitamura; Kenichi Ohashi (PLoS ONE, 2014)
This study investigated the proteome modulated by oncogenic KRAS in immortalized airway epithelial cells. Chloride intracellular channel protein 4 (CLIC4), S100 proteins (S100A2 and S100A11), tropomyosin 2, cathepsin L1, integrinsα3, eukaryotic elongation factor 1, vimentin, and others were discriminated. We here focused on CLIC4 to investigate its potential involvement in carcinogenesis in the lung because previous studies suggested that some chloride channels and chloride channel regulators could function as tumor suppressors. CILC4 protein levels were reduced in some lung cancer cell lines. The restoration of CLIC4 in lung cancer cell lines in which CLIC4 expression was reduced attenuated their growth activity. The immunohistochemical expression of the CLIC4 protein was weaker in primary lung cancer cells than in non-tumorous airway epithelial cells and was occasionally undetectable in some tumors. CLIC4 protein levels were significantly lower in a subtype of mucinous ADC than in others, and were also significantly lower in KRAS-mutated ADC than in EGFR-mutated ADC. These results suggest that the alteration in CLIC4 could be involved in restrictedly the development of a specific fraction of lung adenocarcinomas. The potential benefit of the proteome modulated by oncogenic KRAS to lung cancer research has been demonstrated.